Regional integration Southern Africa - Moyo, Busani; Kwarambo, Marko; Nchake, Mamello (International Food Policy Research Institute, 2020)
This chapter examines agricultural trade integration in Southern Africa, focusing on SADC. We begin with a brief description of the evolution of SADC, followed by a detailed description and analysis of SADC agricultural trade flows and patterns and of possible drivers of the observed trade patterns. The next section discusses the evolution of regional trade agreements in Southern Africa with particular focus on SADC, and the following sections discuss trade integration in SADC, focusing on agricultural trade and possible explanations for the observed trade patterns and flows.